Sonochemical synthesis of Dy-doped ZnO nanostructures and their photocatalytic properties - Oranuch Yayapao (2018)
Dy-doped ZnO nanostructures were synthesized by a sonochemical method. The concentration effect of Dy on their phase, morphology, optical properties and photocatalytic activities was investigated. XRD patterns indicated that the as-synthesized 0-3% Dy-doped ZnO was hexagonal wurtzite structure. SEM and TEM show that the products were nanorods with their growth direction along the c axis. The photoluminescence spectrum of 3% Dy-doped ZnO, applied by Gaussian analysis, consists of three emission peaks at 376 nm, 448 nm and 487 nm. The photocatalytic activities of the as-synthesized products were determined from the degradation of methylene blue (C 16 H 18 N 3 SCl) by UV radiation. In this research, the 3% Dy-doped ZnO showed the highest photocatalytic activity. © 2013 Elsevier B.V. All rights reserved.